The Possibility of Legal Protection of Results Obtained by Artificial Intelligence Within the Framework of Related Rights .- - Davtyan, T. (Bulletin of Yerevan University C: Jurisprudence, 2020)
The article analyzes the feasibility and permissibility of providing legal protection for the results obtained by the so-called autonomous Artificial Intelligence in the framework of Intellectual Property Law. Those are results that are similar, comparable, and in some cases even superior to the works created by humans in the field of literature, art or science. It questions whether there is a substantiated need to provide legal protection for the results obtained by autonomous Artificial Intelligence systems at this stage of technological development, and if so, is it possible to provide such protection within the framework of the Concept of Related Rights. The basic provisions and suggestions in the professional literature on this issue are analyzed.